A Phonemic Analysis Between English And Indonesian In English Conversation - Madya Ramadhani; Roni Ripaldi Turnip; Anita Sitanggang (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This study compares and contrasts the phonetic systems of English and Indonesian in the "English Conversation" In order to teach students how to pronounce English with Indonesian phonemes, the research aims to compare and contrast the phonemes in the English Conversation. Ten English consonant phonemes and ten Indonesian consonant phonemes are the focus of this study. A qualitative technique is used in the descriptive-contextual research methodology. Based on the types of phonemes, the technique design compares the phonemes in Text Conversation written in English and Indonesian. The "English Conversation ", which are made up of 10 consonant phonemes, were discovered to share commonalities between the English and Indonesian phonemic systems. Ten consonants in the English Conversation represent the distinctions between the English and Indonesian phonetic systems.